Effects of endothelin-1 in isolated perfused rat heart. - Neubauer, S; Ertl, G; Haas, U; Pulzer, F; Kochsiek, K (1990)
We examined the effects of the vasoconstrictor peptide endothelin-1 in the isolated heart and defined interactions of endothelin-1 with other hormone systems. Isolated isovolumic rat hearts were perfused with Krebs-Henseleit buffer at constant pressure. First, the effect of a single bolus of endothelin-1 (4-400 pmol) was followed for 90 min. The effect of high dosages (40 and 400 pmol) of endothelin-1 on coronary flow was biphasic, with an early vasodilator and a late vasoconstrictor component that was irreversible. Second, cumulative dose-response curves were obtained for endothelin-1 boluses of 0.04-400 pmol. Coronary flow declined with increasing dosages and was almost abolished at 400 pmol. Neither alpha- nor beta-blocking agents (phentolamine and propranolol) nor the Ca2(+)-channel blocker nifedipine altered the effects of endothelin-1, but prostaglandin synthesis inhibition by indomethacin significantly augmented vasoconstriction by endothelin-1. Angiotensin-converting enzyme (ACE) inhibition by captopril antagonized endothelin-1-dependent vasoconstriction to a small extent at 400 pmol. Coronary constriction due to endothelin-1 could not be reversed by nitroglycerin. We conclude that in isolated rat heart endothelin-1 causes marked and long-lasting coronary constriction. The effect is not influenced by sympathetic and Ca2(+)-channel blockade, is enhanced by prostaglandin synthesis inhibition, and is reduced by ACE inhibition.